Langmuir-Hinshelwood-Hougen-Watson Heterogeneous Kinetics Model for the Description of Fe (II) Ion Exchange on Na-X Zeolite - Kamal, S. K.; Abbas, A. S. (Engineering, Technology & Applied Science Research, 2022)
This study aimed to investigate the kinetics of the anion exchange step of ferrous ions with Na-X zeolite in a temperature range of 20 and 80°C for a period of up to 8 hours. A ferrous sulfate heptahydrate solution was used as a ferrous ion source to exchange with the sodium of the Na-X zeolite. The results showed a change in the physical appearance of the zeolite with the progress of the ion exchange process. The catalyst color was observed with the progress of the ion exchange time and changed from yellow to brown. The ferrous ion exchanged contents increased with temperature and reached 0.519 at 80°C after 8 hours. A kinetic model based on the Langmuir-Hinshelwood-Hougen-Watson model was suggested and developed to describe the ion-exchange process. The proposed model was solved numerically, and the results indicated its ability to describe the experimental results with high correlation coefficients. Finally, the activation energy for the forward reaction was 31590.7J/mole compared to 28105.5J/mole for the backward, and the frequency factors for the forward and backward reactions were investigated.